2017
DOI: 10.1002/wmh3.247
|View full text |Cite
|
Sign up to set email alerts
|

Social Media Engagement With Cancer Awareness Campaigns Declined During the 2016 U.S. Presidential Election

Abstract: Cancer awareness campaigns compete with other health and social issues for public attention. We examined whether public engagement with breast cancer and prostate cancer declined in 2016 during the U.S. presidential election compared to 2015 on Twitter and Google Trends. We found that attention to breast cancer and prostate cancer declined in 2016 before the election as compared to 2015 in Twitter posts and Google searches. The findings suggest that cancer information seeking behavior, passive exposure to heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 25 publications
1
10
0
1
Order By: Relevance
“…Furthermore, our results might be skewed with respect to the timeframe of the study, which was just after the measles outbreak in California Disneyland and it would therefore be interesting to carry out the analysis over a more longitudinal timeframe and also without assuming each user (including each bot user) to have same opinion. However, work by Vraga et al (2017) on the discussion of cancer in social media showed peaks of traffic during awareness months and little in other time frames, which could be broadly considered similar to the disease outbreak studied here. In addition, as Bello-Orgaz et al (2017) found that influential users (i.e., those with high degree centrality) are often in pro-vaccine communities and Love, Himelboim, Holton, & Stewart (2013) discovered that no particular subject is dominating the vaccine conversation in Twitter, it would, therefore, be interesting for future research to explore whether "influential" users are more of those with high degree centrality or those who they agree, and thus understand what defines a user to be influential in the context of anti-vaccination or other highly divided online discussions (Cha, Haddadi, Benevenuto, & Gummadi, 2010).…”
Section: Contribution Discussion and Future Worksupporting
confidence: 59%
“…Furthermore, our results might be skewed with respect to the timeframe of the study, which was just after the measles outbreak in California Disneyland and it would therefore be interesting to carry out the analysis over a more longitudinal timeframe and also without assuming each user (including each bot user) to have same opinion. However, work by Vraga et al (2017) on the discussion of cancer in social media showed peaks of traffic during awareness months and little in other time frames, which could be broadly considered similar to the disease outbreak studied here. In addition, as Bello-Orgaz et al (2017) found that influential users (i.e., those with high degree centrality) are often in pro-vaccine communities and Love, Himelboim, Holton, & Stewart (2013) discovered that no particular subject is dominating the vaccine conversation in Twitter, it would, therefore, be interesting for future research to explore whether "influential" users are more of those with high degree centrality or those who they agree, and thus understand what defines a user to be influential in the context of anti-vaccination or other highly divided online discussions (Cha, Haddadi, Benevenuto, & Gummadi, 2010).…”
Section: Contribution Discussion and Future Worksupporting
confidence: 59%
“…Social media analytics may also reveal which health issues and which at‐risk populations are not participating in online conversations and are therefore missing out on opportunities for health education. For example, data analyses might show gender gaps in which health issues receive online attention (Vraga et al, 2018) or identify when media engagement about a health issue is being displaced by political campaigns (Vraga et al, 2017). Understanding what information about a public health issue is missing on social media enables organizations to update their communication strategies.…”
Section: Opportunity: Evaluating Communication Impactmentioning
confidence: 99%
“…Although social media is a powerful tool for health communication, some empirical evidence has demonstrated that in some cases, social media health communication fails to motivate the target audience's engagement in the health issue at hand [3,4]. This is due to several factors, such as users' skepticism about the accuracy of the information, cultural factors, privacy concerns, and users' preoccupation with other issues [5][6][7][8]. Consequently, the healthcare organization misses out on the chance to bring positive social change in the societies it serves.…”
Section: Introductionmentioning
confidence: 99%